2017
DOI: 10.1097/nmd.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Negative Consequences of Family Caregiving for Veterans With PTSD and Dementia

Abstract: Recent research shows veterans with posttraumatic stress disorder (PTSD) are twice as likely as other veterans to develop dementia. However, no studies to date have examined the impact of co-existing PTSD and dementia on family caregivers, who provide the majority of care to these veterans. Using the Stress Process Model, the current investigation explored the similarities and differences in psychosocial, health, and service use outcomes among caregivers assisting veterans with PTSD and dementia compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Authors suggest that damage to these neural pathways by neurodegenerative processes may weaken the amygdala's frontal inhibitory activity over traumatic memories and is responsible for the resurgence of PTSD in dementia. 5,18 With the temporally graded retrograde amnesia that preferentially spares more distant memories in AD, patients often act as if they have returned to past events, which might have been traumas. In addition, losing selfcapacities and being dependant on others for basic needs can re-enact episodes of traumatic helplessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggest that damage to these neural pathways by neurodegenerative processes may weaken the amygdala's frontal inhibitory activity over traumatic memories and is responsible for the resurgence of PTSD in dementia. 5,18 With the temporally graded retrograde amnesia that preferentially spares more distant memories in AD, patients often act as if they have returned to past events, which might have been traumas. In addition, losing selfcapacities and being dependant on others for basic needs can re-enact episodes of traumatic helplessness.…”
Section: Discussionmentioning
confidence: 99%
“…4 Chronic stress, associated with elevated cortisol, can result in hippocampus atrophy. 4,5 PTSD modifies the hypothalamic-pituitary-adrenal axis and is linked to pro-inflammatory immune alterations, both associated with an increased risk for cognitive decline. 6 Dementia is associated with worsening PTSD symptoms, 7 latelife resurgence, 8 or de novo emergence of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…While some research has demonstrated positive emotional gains for caregivers (Cohen, Colantonio, & Vernich, ), other research studies have repeatedly shown that many caregivers have an increased risk of experiencing depression, grief, fatigue, and physical health problems secondary to exhaustion and self‐neglect (Carter, Golant, & Easom, ; National Alliance for Caregiving, ). Caregivers of wounded (visible and invisible injuries) individuals who might also have other possible traumatic injuries (polytrauma) that occurred while serving face additional, unique challenges (Griffin et al., ; Pinciotti et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Pinciotti et al . () found that family caregivers of veterans with PTSD and dementia are at greater risk of negative consequences than those of veterans with dementia only. There were also an increased number of neuropsychiatric behaviour problems found in veterans with PTSD and dementia, increased memory problems, and greater physical health strain on the family caregivers contributed to this risk (Pinciotti et al .…”
Section: Theme 1: Symptomatic Expression Of Ptsd and Dementiamentioning
confidence: 99%
“…Veterans with PTSD and dementia are known to incur increased healthcare expenses (Veitch et al 2013). For example, caregivers of veterans with PTSD and dementia also use more types of in-home and community services than those with dementia only (Pinciotti et al 2016). Additionally, it is expected that there will be a significant increase in demand for long-term care of veterans with dementia in the next decade (Lemke & Schaefer 2010).…”
Section: Theme 3: Implications For Health-care Providers and Treatmenmentioning
confidence: 99%